New public management and alternative service delivery in senior citizen care services - Mohd Alwi, Norhayati; Alias, Intan Aidura; Mat Yasin, Fatimah (2019)
Many governments are facing financial challenges that call for a reduction in public spending. One way to address this challenge is to adopt new public management (NPM). Under NPM, alternative service delivery (ASD) provides opportunities to third parties to be involved in the provision of services. Generally, the objective of this study is to provide some insights on the business model of ASD under the NPM for senior citizen care services. Specifically, the study highlights the level of involvement of third party as well as the financial sustainability and challenges that the third party might be facing when providing senior citizens care services. This study collects data on the financial sustainability of 16 NGOs that are providing senior citizen residential care services around Peninsular Malaysia. Survey questionnaires were given to assess their financial sustainability. The top management of the NGOs was also interviewed to obtain further insights. The study highlighted that the NGOs rely on several financial resources to manage the care services. Most of the centres have minimal facilities and a small number of staff. The findings of the study may guide the proposed business model and strategies for ASD implementation in senior citizen care services